Desain Aktivitas Dan Lingkungan Kerja Pada Kinerja Keseluruhan Pekerja Melalui Kepuasan Lukisan PT. Lembaga Keuangan Departemen Kalbar Nanga Pinoh - Chaerul Haryono; Muhammad Ridwan Basalamah; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This take a look at objectives to observe the impact of job layout and paintings surroundings on worker overall performance mediated by activity delight (have a look at on PT financial institution Kalbar department Nanga Pinoh). This kind of research is explanatory studies the usage of a quantitative approach. The populace on this have a look at have been employees of PT. bank Kalbar branch Nanga Pinoh. The sampling technique was satured sampling, which took the entire sample of 36 respondents. The facts used in this study is number one data, specifically by using distributing questionnaires. The measurement scale used is a likert scale. studies facts have been analyzed using IBM SPSS S.26. The outcomes of this look at located there may be an instantaneous impact of job layout and paintings environment to process satisfaction, there's an instantaneous effect of task design to worker performance however on paintings surroundings to worker overall performance there may be no direct effect, there is an instantaneous impact of task satisfaction to worker performance, there may be an immediate impact of activity design and paintings environment thru job pleasure to worker overall performance. Keywords: Activity Design, Paintings Surroundings, Task Pride, Employee Overall Performance